PENGARUH OPINI AUDIT DAN TEMUAN AUDIT BPK TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI RIAU - Yolanda Rasyid; Rama Gita Suci; Annie Mustika Putri (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
This study aims to examine the effect of the audit opinion and BPK audit finding on the performance of local goverment in district/cities in  Riau Province. The population in this study consisted of 12 districts/cities in Riau province with an observation period of 2016-2020. The sampling method in this study uses a non-probability sampling technique, namely a sampling method that does not provide equal opportunities or opportunities for each member of the population to be selected as a sample. The non-probability sampling method used is saturated sampling and the number of samples in the study is 60 samples. The test was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach with the help of WarpPLS version 7.0 software used in data analysis and hypothesis testing. The results of the study found that audit opinions and audit findings have a negative effect on local government performance. This research has implications for local governments to have policies in regional financial management that are in accordance with statutory regulations so that they can make their local government performance better.Keywords : Audit Opinion, BPK Audit Finding, and Local Goverment Performance.